an investigation into linguistic expressions of interpersonal meaning in english at graduation ceremonies. - Trần Thị Thanh Hiệp (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The purpose of the study is to find out linguistic expressions of interpersonal meaning in English at graduation ceremonies. The model adopted for this paper is Halliday‘s systemic functional linguistics (SFL), mainly, interpersonal function. The speeches at the commencement address are masterpieces that are well-known around the world. It is a potential source of interpersonal meanings with their own features. This paper explores the interpersonal meaning of mood, modality. The paper draws a conclusion that the Hallidayan approach can be applied to some extent to teaching and learning English.